Produktivitas Varietas Padi dari Kelas Benih Berbeda - Sri Wahyuni; Indria W. Mulsanti; Satoto Satoto (Puslitbang Tanaman Pangan, 2013)
Seed certification system in Indonesia applies the four seed classes, i.e. Breeder Seeds (BS), Foundation Seeds (FS), Stock Seeds (SS) and Extension Seeds (ES). Farmers should plant the Extension Seeds for producing rice grain. However, farmers in some provinces prefer to use the Stock Seeds to produce rice grain, due to false information that higherseed-class will produce higher grain yield. The purpose of seed certification is to ascertain genetic identity and genetic purity, so as the potential genetic of the variety could be expressed maximally in rice field. Moreover, grain yield is influenced by the genetic factor and the environment condition. Previous research had indicated that the seed quality of higher seed classes was not always better than that of the lower seed class. Furthermore, rice crop planted from higher seed class of the same variety did not showed any differences in appearances of its agronomic characters (plant height, number of tillers) and yield components (grain weight, panicle length, filled grains per panicle), nor the grain yield. The notation that higher seed class produces higher grain yield, as was commodity believed by farmers and other stake holders, was incorrect. Seed certification is designed to ascertain the genetic purity of variety, but not to increase the productivity of the respective variety.